HEALTH WORKERS' BEHAVIOR IN MEDICAL WASTE SORTING AT HOSPITAL - Ika Nurhayati; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
Medical waste is an infectious and hazardous material that health services, including hospitals, produce. Health workers risk spreading disease due tomproper medical waste management. The study aims to provide an overview of health workers sorting medical waste. This research is qualitative research with a case study design. Ten Informants, health workers, midwives, nurses, and general practitioners were participants in this study. Interviews and data collection data were analyzed by content analysis. The interviews with health workers related to the period of work and the period of service give positive or negative influences such as having more experience in their duties or causing feeling bored. The result of the Interviews related to health workers' knowledge good. Almost every day, Infection Prevention Control (PPI) officers observe medical waste sorting and still find health workers who have not implemented medical waste sorting properly. The health workers had a positive attitude towards the sorting of medical waste. Still, because the workload was quite heavy, sometimes they did not pay attention to sorting medical waste, and co-workers did not remind each other. Hospitals should hold continuous socialization by training or workshops as a joint commitment to properly improve medical waste management. Rewards for those who performed medical waste management properly increase motivation for health workers in units, besides sanctions to increase discipline in sorting medical waste.